2021
DOI: 10.56899/151.01.26
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Properties of Selected Fruit-bearing and Underutilized Tree Species in the Philippines

Abstract: To help augment the raw material supply of the wood-based industries, the study evaluated the physical and mechanical properties (PMP) of six selected timber species in the Philippinesfour fruit-bearing and two underutilized tree species. The fruit-bearing species were "nangka" (Artocarpus heterophyllus Lamk.), "santol" [Sandoricum koetjape (Burm. F.)], "durian" (Durio zibethinus Murray), and "marang" [Litsea perrottetti (Blume) F. Vill.] collected from Bislig, Surigao del Sur (Caraga Region, Mindanao), while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…Likewise, Özçifçi et al (2007) found that boric acid treatments negatively affected the shear strength of phenol–formaldehyde-bonded pine, beech, and poplar joints. Similar to the findings in this study, negative impacts of DOT on adhesive-bond shear strength were reported by Alipon et al (2018) on polyvinyl acetate, urea–formaldehyde, and phenol–formaldehyde bonds in bamboo wood composite; and by Vick et al (1990) on phenol–formaldehyde-bonded aspen veneer. There is also literature evidence that both boron- (Alamjuri et al 2010) and copper-based treatments (Miyazaki and Nakano 2002; Frihart 2003) accelerate or inhibit adhesive cure on preservative-treated woods.…”
Section: Resultssupporting
confidence: 91%
“…Likewise, Özçifçi et al (2007) found that boric acid treatments negatively affected the shear strength of phenol–formaldehyde-bonded pine, beech, and poplar joints. Similar to the findings in this study, negative impacts of DOT on adhesive-bond shear strength were reported by Alipon et al (2018) on polyvinyl acetate, urea–formaldehyde, and phenol–formaldehyde bonds in bamboo wood composite; and by Vick et al (1990) on phenol–formaldehyde-bonded aspen veneer. There is also literature evidence that both boron- (Alamjuri et al 2010) and copper-based treatments (Miyazaki and Nakano 2002; Frihart 2003) accelerate or inhibit adhesive cure on preservative-treated woods.…”
Section: Resultssupporting
confidence: 91%